PENGARUH SEDIMENTASI TERHADAP TERUMBU KARANG DI KAWASAN KONSERVASI LAUT DAERAH BINTAN TIMUR KEPULAUAN RIAU - Adriman Adriman; Ari Purbayanto; Sugeng Budiharso; Ario Damar (Fakultas Perikanan dan Kelautan, Universitas Riau, 2013)
The objectives of this study is to analyze efect of sedimentation on coralreef in RMCA Bintan Timur. A survey on rate sedimentation and ecosystem coralreef condition has been conducted in Regional Marine Conservation Area(RMCA) Bintan Timur. Eleven station were selected for the observace andmeasurement. Efect of sedimentation on coral reef analysis conducted by themethod of regression. The results showed that the sedimentation influcednegatively of life coral reef in RMCA Bintan Timur.Keywords: sedimentations, coral reef ecosystem, regression, Bintan Timur